PID vs. Reinforcement Learning: A Comparative Study on Autonomous Driving in the Gymnasium Car Racing Environment (Development Engineering Conferences Center Articles Database, 2025)
In this paper, we investigate two distinct control strategies for autonomous vehicles navigating tracks: Proportional-Integral-Derivative (PID) control and Proximal Policy Optimization (PPO). We compare their feasibility and computational efficiency and introducing a novel approach for longitudinal and lateral control within the CarRacing environment of OpenAI’s Gymnasium. While deep reinforcement learning methods, such as PPO, have demonstrated significant potential in the control domain, they often require substantial computational resources and time due to the inherent exploration-exploitation trade-off. Our findings suggest that, in certain scenarios, classical control techniques like PID offer greater reliability and ease of implementation.